Investigating the Influence of training religious coping skillson resiliency, adaptability and stress management in veterans\' spouses - S. Askaryan; M.J. Agheri; M.H. Hassan Zadeh (Afarand Scholarly Publishing Institute, 2014)
Background & Purpose: The purpose of this article is to study the effect of training religious coping skills on Resiliency and adaptability components and stress management in veteranschr('39') spouses. Methods & Materials: This study is quasi-experimental. Statistical population included 70 veteranschr('39') spouses whose children were studying in Shahed primary school of Mashhad in district5, in 1392-1391education year. For sampling, Available method was used and all the testees were given Connor & Davidson Resilience Questionnaire and bar-on emotional intelligence Questionnaire for investigating two components.30 spouses, results who gained the lowest score in both tests, were selected after the Survey. The testees were divided to two Equal experiment and control groups, through random assignment. Then experiment group was provided religious coping skills training with the Islamic approach in10 sessions. Finally, a post-test was taken from both groups. Results: The data analysis was performed, for obtaining covariance and Pearson correlation test. Results show a meaningful measure of 0.01 and variables showed direct relationship to the testing component in Pearson correlation test therefore it can be concluded that training of religious coping skills may be useful for veteranschr('39') spouses on their resiliency, adaptability. Conclusion: On the basis of the results of this study, It is concluded that training spouses of veterans, religious coping skills can be effective in Improving their level of mental health and empowering them to deal with their problems.